Activated Protein C Resistance (FV:Q506) and Pregnancy - Lindqvist, Pelle G.; Svensson, Peter J.; Maršál, Karel; Grennert, Lars; Luterkort, Marie; Dahlbäck, Björn (Thrombosis and Haemostasis, 1999)
Activated protein C (APC) resistance, due to a point mutation in the factor V gene (FV:Q506), is a major risk factor for venous thromboembolism. To determine the prevalence of APC resistance in a large series of pregnant women, and to elucidate its obstetric consequences, we performed a prospective study in Malmö, Sweden, comprising 2,480 women enrolled in early pregnancy. The presence of APC resistance (the FV:Q506 allele) was determined. The women were interviewed about their medical histories including venous thromboembolic events (VTE) in relatives. The outcome variables were the VTE rate, intrapartum blood loss, and the prevalence of selected pregnancy complications such as fetal loss, pre-eclampsia, and intrauterine growth retardation.The overall prevalence of APC resistance was 11% (270/2480). The APC-resistant subgroup did not differ significantly from the non-APC-resistant subgroup in terms of pregnancy complications, but was characterized by an 8-fold higher risk of VTE (3/270 vs. 3/2210), a lower rate of profuse intrapartum haemorrhage (3.7% vs. 7.9%) (p = 0.02), and less intrapartum blood loss (340 ml vs. 361 ml) (p = 0.04). Despite the high prevalence of APC resistance in this series of gravidae (11%), its presence was unrelated to adverse pregnancy outcome apart from an 8-fold increased risk of VTE.